Dynamic Interdependence and Volatility Transmission in Turkish and European Equity Markets - Huseyin Tastan (Turkish Economic Association, 2005)
This paper investigates dynamic interdependence, price and volatility transmissions and financial integration between Turkey and major equity markets in EU and USA. We attempt to quantify the dynamic relationship among developed stock exchanges of Germany, France, Britain, US and Turkey, an important emerging market. Using daily data on stock prices we analyze price and volatility spillovers in a vector autoregression-dynamic conditional correlations-multivariate generalized autoregressive conditional heteroskedacticity (VAR-DCC-MVGARCH) framework. This approach enables us to measure the extent to which these equity markets are interrelated by taking into account the time-varying variance-covariance structure. Since the major trade partners of Turkey are EU countries it is of interest to examine any changes in the structure of volatility spillovers. To this end, we analyze the effects of customs union agreement between Turkey and EU on the dynamic interdependence of stock markets by dividing the sample into two periods. The analysis reveals that, although they are small in magnitude as compared to their counterparts in developed markets, the conditional correlations can be assumed to be constant in the pre-customs union agreement while it fluctuates significantly in the post-customs union agreement.
Keywords: 330